Search for exotic particles (Q-balls) in ultra-high-energy Astroparticles - Paula, Tales Ferraz de (2023)
This dissertation was proposed in the scenario of studying candidates for the origins of ultra-high-energy cosmic rays. The main goal is to study exotic air showers induced by Q-balls and to develop a method to differentiate exotic-induced air showers from proton-induced ones in the energy range from 1017.0 to 1021.0 eV. The first part of the study was done with the analysis of longitudinal profiles of air showers simulated with CONEX for more than seventeen thousand events simulated. In the second part, a method is proposed that is compatible with the event-analysis chain of the Pierre Auger Observatory. The first results are divided in three parts, based on the three simulation groups that were done. The first result from the simulation study allowed the proposal of another fit function hypothesis to describe the exotic-induced shower, along with the Gaisser-Hillas function, typically used to describe the profile of hadronic-induced showers. The second result allowed a fully unambiguously classification based on the goodness-of-fit method X2/ndf value when comparing both fitted functions for each primary particle. The third result from simulated events analysis showed independence of energy deposit rate from primary energy for exotic-induced showers, allowing a parametrization proposal for the energy deposit rate with Q-balls cross-section. The second part of results was to apply the proposed method to Pierre Auger Observatory, by testing it on the Observatorys Offline. A new module was proposed for it and a initial test was performed. It is shown that, even after taking into account all the detector and geometry effects related to the fluorescence-based detection of extensive air showers, the classification of exotics is still possible, hinting to the success of the method. Further study, however, is necessary to fully test and validate the method, and the next steps were then discussed.